Glutathione peroxidase 3 (GPX3) suppresses the growth of melanoma cells through reactive oxygen species (ROS)‐dependent stabilization of hypoxia‐inducible factor 1‐α and 2‐α. Issue 11 (16th July 2019) - Yi, Zihan; Jiang, Lu; Zhao, Lei; Zhou, Meiling; Ni, Yueli; Yang, Yuye; Yang, Huixin; Yang, Lijuan; Zhang, Qiao; Kuang, Yingmin; Deng, Mingjia; Zhu, Yuechun
Abstract: In this study, we aimed to explore the mechanism of glutathione peroxidase 3 (GPX3) in the growth of malignant melanoma (MM) cells by hypoxia‐inducible factor‐1α (HIF1‐α) and HIF2‐α regulating the metabolism through reactive oxygen species (ROS). The messenger RNA and protein expression of GPX3, HIF1‐α, HIF2‐α in tissues, and cell lines were measured by reverse transcription‐quantitative PCR and Western blot analysis. A375 cells were transfected with GPX3 overexpression plasmid, small interfering RNA (siRNA) targeting GPX3, or siRNA targeting HIF1‐α/HIF2‐α to upregulate or downregulate the expression of GPX3 or HIF1‐α/HIF2‐α. The effects of H2 O2 and N‐acetylcysteine (NAC) on the levels of HIF1‐α and HIF2‐α after overexpression of GPX3 were studied. The cell viability was detected by Cell Counting Kit‐8. The levels of ROS, glucose uptake and lactic acid production, oxidative phosphorylation, and glycolysis of cells were measured for assessment of cellular metabolism. The expression of GPX3 decreased, while ROS, HIF1‐α, and HIF2‐α increased in MM tissues and cells. Overexpression of GPX3 inhibited the viability of MM cells and the growth of melanoma xenografts. The overexpression of GPX3 reduced the glucose uptake, extracellular lactic acid content, and extracellular acidification rate and increased the oxygen consumption rate level. Overexpression of GPX3 could reduce the levels of HIF1‐α and HIF2‐α, which could regulate metabolic levels. GPX3 reduced ROS level in MM to inhibit HIF1‐α and HIF2‐α. The addition of H2 O2 increased while NAC reduced the protein levels of HIF1‐α and HIF2‐α in the cells overexpressing GPX3. Our study demonstrates that GPX3 inhibits the growth of MM cells through its inhibitory effect on cell metabolic disorder by inhibiting HIF1‐α via regulating ROS. Abstract : 1. Glutathione peroxidase 3 (GPX3) is low expressed, while levels of reactive oxygen species (ROS) and hypoxia‐inducible factor‐1α (HIF1‐α) increased in malignant melanoma (MM). 2. GPX3 can inhibit the growth of MM. 3. GPX3 can inhibit HIF1‐α by decreasing ROS level. 4. GPX3 can inhibit glucose uptake, extracellular lactic acid content, oxygen consumption rate, and extracellular acidification rate. 5. GPX3 regulates the metabolism of MM cells by regulating CHCHD4 and ROS expression.